From Purification Movement to Social Philanthropy: The Transformation of PERSIS in the Management of ZIS for Mustahik Empowerment - Aang Gunaepi; Duski Ibrahim; Arne Huzaimah; Ryan Bianda; Pathur Rahman; Alimron Alimron (RUSYDIAH: Jurnal Pemikiran Islam, 2026)
This article analyzes the transformation of PERSIS in managing community funds through LAZ PERSIS and its implications for the empowerment of mustahik. This study employs a qualitative approach using a single instrumental case study design. Data were collected through in-depth interviews, field observations, and analysis of institutional documents. The study indicate that the transformation of PERSIS does not diminish its identity of doctrinal purification, but rather expands the articulation of its movement into the socio-economic sphere through more professional governance of zakat, infaq, and sadaqah. LAZ PERSIS serves as an institutional space for this transformation by strengthening transparency, accountability, empowerment programs, and the distribution of community funds. However, the empowerment process continues to face challenges in terms of follow-up, monitoring, and program impact measurement. This article contributes to the study of Islamic organizational transformation and Islamic philanthropy by demonstrating the relationship between institutional change, ZIS governance, and the empowerment of mustahik.